THE INFLUENCE OF LEVERAGE, INDEPENDENT COMMISSIONERS, COMPANY ACTIVITIES AND PROFITABILITY ON SUSTAINABILITY REPORT DISCLOSURES - Ho, Vina; Kampo, Kunradus; Tangke, Paulus (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2023)
Purpose – This study aims to examine and analyze the influence of leverage, independent commissioners, company activities, and profitability on disclosure of sustainability reports. The theory used in this research is stakeholder theory and agency theory Design/methodology/approach – The type of research used in this research is explanatory research Findings – The results of the study show that leverage has a positive and significant effect on sustainability report disclosure. The proportion of independent commissioners has a positive and significant effect on the disclosure of the sustainability report. The company's activities have no effect on the disclosure of the sustainability report. Profitability has a positive and significant influence in increasing the disclosure of sustainability reports. Originality – The population is property companies listed on the Indonesia Stock Exchange (IDX) in 2019 to 2021, totaling 79 companies using a purposive sampling method Keywords: Leverage, Independent Commissioner, Company Activity, Profitability, Disclosure of Sustainability Report Paper Type Research Result